A nonclonal outbreak of vancomycin-sensitive Enterococcus faecalis bacteremia in a neonatal intensive care unit. (5th August 2019) - Kotsanas, Despina; Tan, Kenneth; Scott, Carmel; Baade, Britta; Cheng, Michaela Hui Ling; Tan, Zien Vanessa; Taylor, Jacqueline E.; Kwong, Jason C.; Seemann, Torsten; Coombs, Geoffrey W.; Howden, Benjamin P.; Stuart, Rhonda L.
Abstract: Objective: To describe an outbreak of bacteremia caused by vancomycin-sensitive Enterococcus faecalis (VSEfe). Design: An investigation by retrospective case control and molecular typing by whole-genome sequencing (WGS). Setting: A tertiary-care neonatal unit in Melbourne, Australia. Methods: Risk factors for 30 consecutive neonates with VSEfe bacteremia from June 2011 to December 2014 were analyzed using a case control study. Controls were neonates matched for gestational age, birth weight, and year of birth. Isolates were typed using WGS, and multilocus sequence typing (MLST) was determined. Results: Bacteremia for case patients occurred at a median time after delivery of 23.5 days (interquartile range, 14.9–35.8). Previous described risk factors for nosocomial bacteremia did not contribute to excess risk for VSEfe. WGS typing results designated 43% ST179 as well as 14 other sequence types, indicating a polyclonal outbreak. A multimodal intervention that included education, insertion checklists, guidelines on maintenance and access of central lines, adjustments to the late onset sepsis antibiotic treatment, and the introduction of diaper bags for disposal of soiled diapers after being handled inside the bed, led to termination of the outbreak. Conclusions: Typing using WGS identified this outbreak as predominately nonclonal and therefore not due to cross transmission. A multimodal approach was then sought to reduce the incidence of VSEfe bacteremia.